If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6 = 3r + -1(-3) Multiply -1 * -3 6 = 3r + 3 Reorder the terms: 6 = 3 + 3r Solving 6 = 3 + 3r Solving for variable 'r'. Move all terms containing r to the left, all other terms to the right. Add '-3r' to each side of the equation. 6 + -3r = 3 + 3r + -3r Combine like terms: 3r + -3r = 0 6 + -3r = 3 + 0 6 + -3r = 3 Add '-6' to each side of the equation. 6 + -6 + -3r = 3 + -6 Combine like terms: 6 + -6 = 0 0 + -3r = 3 + -6 -3r = 3 + -6 Combine like terms: 3 + -6 = -3 -3r = -3 Divide each side by '-3'. r = 1 Simplifying r = 1
| 2-(-3p)=11 | | r/3-2=1 | | 2/3u-3/2=-1/5 | | 14=4k+2 | | v(v)+3v-18=0 | | 10(x-2)/5x-10 | | 3(4x+6)=9x+122 | | (5u-4)(3-u)=0 | | -6(c+1)-(6+5c)= | | (2x+3)+(4x+8)=180 | | =(y+6u)(7y-7u-5) | | -12x-20=-10x-15 | | -2x-10=3x-15 | | fn=5n+6 | | 16x-10+9=99-30x | | 6cosx+5=-5cosx+14 | | x+.05x=252000 | | (6x-5)(8x+3)=0 | | 187=-x+8 | | x+.05x=456 | | x+.05x=110 | | f(x)=x^3-6x^2-x+6 | | p^6-1=0 | | Y=-14x*-70x | | 2x/11 | | 3x+6x+2=-4x | | 10+10x=50+2x | | 8+w-4.7w-.5= | | 15x^2+26x+7= | | 125x^6-8=equation | | -4/9x=8 | | 5/√5xy^2 |